Working with Patients Living with Obesity in the Intensive Care Unit: A Study of Nurses’ Experiences - Shea, Jacqueline M. (Université d'Ottawa / University of Ottawa, 2014)
Nurses who work in the intensive care settings (or units, ICU) in Canada encounter a growing number of patients living with obesity (PLWO) in clinical practice. Many authors suggest that the number of PLWO who are admitted to the ICU has increased significantly because obesity is on the rise in Canada. PLWO are thought to be at a higher risk for developing chronic illnesses and life-threatening complications that require an admission to the ICU. They are also more likely to develop postoperative complications that require life-sustaining treatments, invasive hemodynamic monitoring and evaluation, assistive devices, pharmacological interventions, parenteral nutrition, fluid and electrolyte management, and prolonged admission with associated risks of complications. Yet, there is limited research on the experience of nurses providing care to PLWO. The goal of this qualitative study was to examine the experiences of ICU nurses who work with PLWO and how these experiences affect the way they provide care. More specifically, this study was designed to describe and explore the inclusionary and exclusionary practices developed by nurses providing care to PLWO by drawing Canales’ (2000) Othering framework. Lastly, an additional goal of this study was to document the needs of ICU nurses with respect to the care of PLWO and areas of improvement in the ICU. A total of 11 ICU nurses were interviewed for this study. Data analysis followed the principles of Applied Thematic Analysis (ATA) and revealed four themes. The first theme describes how the PLWO become “Other” in the ICU context. The second theme focuses on exclusionary Othering and how it manifests itself in the way PLWO are differentiated, cared for, and viewed in the ICU context. The third theme sheds light on inclusionary Othering in the form of strategies that are used by ICU nurses to engage with PLWO in a way that is inclusive and transformative. Finally, the last theme concentrates on the ICU environment itself and the resources available (or not available) to nurses, with a particular emphasis on the needs of nurses who provide care to PLWO.
Keywords: ICU; Intensive Care; Nurses; Nursing; Obesity; Othering